Photocatalytic Degradation of Ciprofloxacin by GO/ZnO/Ag Composite Materials - Haonan Chi; Pan Cao; Qi Shi; Chaoyu Song; Yuguang Lv; Tai Peng (Nanomaterials)
This study synthesized graphene oxide (GO)/zinc oxide (ZnO)/silver (Ag) composite materials and investigated their photocatalytic degradation performance for ciprofloxacin (CIP) under visible light irradiation. GO/ZnO/Ag composites with different ratios were prepared via an impregnation and chemical reduction method and characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). The results demonstrated that under optimal conditions (20 mg/L CIP concentration, 15 mg catalyst dosage, GO/ZnO-3%/Ag-doping ratio, and pH 5), the GO/ZnO/Ag composite exhibited the highest photocatalytic activity, achieving a maximum degradation rate of 82.13%. This catalyst effectively degraded ciprofloxacin under light irradiation, showing promising potential for water purification applications.